Effect of Lactose Hydrolysed Condensed Whey and Bifidobacterium bifidum in Yogurt - Beena A K (Department of Dairy Science, College of Veterinary and Animal Sciences, 1995)
An experiment was conducted to assess the possibilities of utilizing whey solids in the form of condensed whey or lactose hydrolysed condensed whey as a substitute for NDM. Their effect was also studied in conjunction with B. bifidum as a dietary adjunct.